Scale model seismicity: a detailed study of deformation localisation from laboratory acoustic emission data - Graham, Caroline C. (The University of Edinburgh, 2010)
Acoustic emissions (AE) can provide information relating to the internal state of a deforming rock sample during laboratory testing and have been utilised to quantify damage progression for time-dependent failure modeling. However, the underlying physical mechanisms that produce AE in different materials and their evolution during the process of damage localisation are not fully understood, particularly in porous media. In order to investigate the sources of laboratory acoustic emissions, a moment tensor inversion was applied to data from triaxial compression experiments on Aue granite and Clashach sandstone. The moment tensor inversion was verified for granite, by comparison with results obtained using a more simplistic source analysis technique. In the non-porous Aue granite, AE sources exhibited a predominantly tensile behaviour in the early stages of AE activity. However, shear sources become dominant in the vicinity of the peak stress. In contrast, during deformation of the Clashach sandstone, which has a significant pre-existing porosity, AE sources are dominated by a collapse signature and generally involve a notable shear component. AE that have a predominantly shear mechanism are also a major contributor to the microscale deformation imaged by the technique, and dominate during shear localisation. A combination of correlation analysis and source analysis was used to elucidate the temporal and spatial evolution of the AE source mechanisms involved in the localisation process, as well as during a temporary hiatus in the progression to failure. The results support the concept that the cascade to failure requires the simultaneous involvement of a range of micromechanical behaviours to maintain the progression of localised damage, and eventual formation of a fault. Localisation of collapse mechanisms was not observed until the final approach to failure. Finally, AE sources produced during brittle deformation of the Clashach sandstone were characterised in detail and compared to microstructural observations representing the integrated effect of all times up to the end of the test, and including smaller structures that may have been formed insufficiently dynamically to produce AE. Equivalent focal mechanisms for these events are presented and the relative proportions of their volumetric and shear components considered. The results indicate that AE sources display a wide spectrum of micromechanical behaviour that is consistent with microstructural observations, indicating that AE mechanisms are representative of ongoing deformation processes within the sandstone. It is argued that moment tensor inversion of acoustic emissions is a powerful tool for elucidating the micromechanical evolution of damage, during the brittle deformation of rock.
NER/S/A/2005/13745
Keywords: Acoustic emissions; deforming rock; tensor inversion; shear mechanism; deformation